Elderly Great Grand Multipara with Gestational Hypertension and Anemia Managed in a Rural Tertiary Hospital: A Case Report - Shrestha, Uma (Journal of Institute of Medicine Nepal, 2019)
Parity more than five is grand multiparty and more than 10 is great grand multiparity. Women with high birth order are at increased risk for adverse obstetric outcomes. The risk is even higher for great grand multiparous women than grand multiparous women. Grand and Great grand multiparity predispose for adverse maternal and prenatal outcomes such as malpresentation, labor dystocia, caesarean delivery, postpartum hemorrhage, maternal anemia, congenital malformations and perinatal mortality. Grand and Great grand multiparty is also independent risk factor for labor dystocia and perinatal mortality. However, most of the adverse outcomes that have been associated with grand multiparity may actually be confounded by advanced age, less antenatal care and low socioeconomic level. Although pregnancy hypertension is more commonly seen among youngprimigravidas, hypertension is equally common in elderly women. This is a unique case of elderly great grandmultiparous women with moderate anemia who developed gestational hypertension and underwent emergency cesarean section resulting into normal maternal and fetal outcome.